The Power of Sustainable Green Strategy on Companys Financial Performance - Sukiranto Sukiranto; Suhariyanto Suhariyanto; Sumaryo Sumaryo (Penerbit Goodwood, 2025)
Purpose: This study aims to examine; (1) sustainable green strategy on the company's financial performance (CFP) and (2) the role of Political Connections (PC) as a moderator influence of sustainable green strategy on the company's financial performance (CFP). Methodology/approach: Drawing on Triple Bottom Line Theory, the authors developed and tested hypotheses using secondary data using secondary data from 100 Indonesian mining sector observations from 2017 to 2021. The sample used in this study is purposive sampling, and the analysis uses panel data with Eviews 13. Results/findings: The results show that PC significantly reduces the impact of SGS on CFP. Additionally, the research reveals that PC acts as a pure moderating variable. This is consistent with the Triple Bottom Line theory, which asserts that management must balance the various interests of all life aspects by fulfilling the basic right to water as the main internal resource for achieving CFP. Conclusions: Sustainable green strategy has a negative impact on the CSP. The implementation of the PC provides a positive reinforcement to the relationship between SGS and CFP. Limitations: In Indonesia, the adoption of Workplace Assessment Standards is still mostly optional, which leads to many businesses disclosing information below optimal standards. Contribution: This study offers new insights to green strategy makers in enhancing the monitoring role of mining corporations. The study also adds value to the understanding of predicting CFP by using SGS, and the role of PC as moderating influences of this relationship,particularly in an emerging economy like Indonesia.